WEB-BASED MATERIALS FOR EXTENSIVE READING TO PROMOTE STUDENTS’ READING HABIT - Afi Ni'amah; Yunita Puspita Sari (STKIP PGRI Jombang, 2016)
Alongwiththedevelopmentoftechnology,internethasbeencommonlyused inthelearningprocesstoincrease interestinlearning.WebQuestisanInternet-based learningmodelthatisproblem-basedlearningorientedinwhichthe studentsinteract directlywithlearningresourcesviatheInternet.LearningactivitiesthatuseWebQuest is a teaching strategyusedin Literal Reading Courseaimedat improving students’ reading skills. Employinganactionresearch, thestudyshowedthat the materials providedinWebQuestwerenotonlyabletotrainstudentstocomprehendthecontent ofreading,butalsoprovideexposure tothe cultureofthe targetlanguage.Worksheets withproperinstructions werefoundasadeterminantofthesuccessofthestrategyimplementationinimprovingthereadingskillsofstudents